2019
DOI: 10.1101/575993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-linear effects of socioeconomic status on brain development: associations between parental occupation, cortical thickness and language skills in childhood and adolescence

Abstract: Studies have pointed to the role of the brain in mediating the effects of the social environment of the developing child on life outcomes. Since brain development involves nonlinear trajectories, these effects of the child's social context will likely have age-related differential associations with the brain. However, there is still a dearth of integrative research investigating the interplay between neurodevelopmental trajectories, social milieu and life outcomes. We set out to fill this gap, focusing specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…This pattern is suggestive of more prolonged maturational processes in infants from higher-SES backgrounds. Later in development, in youth aged 3–20 years, SES moderates the negative relationship between age and cortical thickness such that youth from lower-SES backgrounds show a steeper curvilinear decrease in cortical thickness at a younger age than do youth from higher-SES backgrounds 22 , 23 . Adolescents aged 12–18 years in low-income households show a steeper curvilinear relationship between age and cortical thickness than do adolescents in high-income households 24 .…”
Section: Structural Brain Developmentmentioning
confidence: 99%
“…This pattern is suggestive of more prolonged maturational processes in infants from higher-SES backgrounds. Later in development, in youth aged 3–20 years, SES moderates the negative relationship between age and cortical thickness such that youth from lower-SES backgrounds show a steeper curvilinear decrease in cortical thickness at a younger age than do youth from higher-SES backgrounds 22 , 23 . Adolescents aged 12–18 years in low-income households show a steeper curvilinear relationship between age and cortical thickness than do adolescents in high-income households 24 .…”
Section: Structural Brain Developmentmentioning
confidence: 99%
“…Accordingly, schools could benefit from including activities in their curricula that stimulate the development of Students’ EFs. This is of special importance for children from lower educated families who may lag behind in the development of EFs because their home environment has not been optimal for the acquisition of skills in this domain ( Rindermann and Baumeister, 2015 ; Khundrakpam et al, 2019 ; Mackes et al, 2020 ). Moreover, results from the present study indicate that not only children from lower LPE families may benefit from such facilities, but also students with behavioral problems in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have been published which make this point in a comparison of children growing up in families from a lower versus higher SES (e.g., Mackes et al, 2020 ; see also Farah, 2018 ). As an example, Khundrakpam et al (2019) found non-linear effects of socioeconomic status on brain development in childhood and adolescence with associations between parental occupation, cortical thickness and language skills. In adolescence, social isolation appeared to disrupt cortical development and goal-dependent decision making ( Hinton et al, 2019 ).…”
Section: Brain Development Learning and The Notion Of Plasticitymentioning
confidence: 99%